Aplikasi Monitoring dan Evaluasi Analisis Kuantitatif Pada Formulir Resume Medis Digital Di SMC RS Telogorejo Semarang tahun 2022 - Agiwahyuanto, Faik; Suyoko, Suyoko; Anjani, Sylvia; Abiyasa, Maulana Tomy; Prasetya, Jaka (Politeknik Negeri Jember, 2024)
Hospital accreditation standards require periodic reviews of medical records as part of performance improvement efforts, with review results being regularly reported to the Hospital Director. A preliminary survey in the Inpatient Department (IRNAP) at Telogorejo General Hospital, Semarang City, conducted from January to February 2022, showed that the implementation of electronic medical records (EMR) for inpatient services began on October 26, 2021. It was found that certain sections, especially in the discharge summary form, were not fully completed by doctors. This study aims to design and develop an application for monitoring and evaluating the quantitative analysis of digital medical discharge forms at SMC Telogorejo Hospital Semarang in 2022. The research employs a descriptive method, analyzing quantitative variables in the EMR. The study population consists of 1,826 inpatient medical records from 2021, with a sample of 183 records selected using purposive sampling. The result of this study is the SIKUMIS application. The development of the SIKUMIS application is crucial in supporting the assurance of medical record service quality, particularly in the analysis of inpatient discharge summaries. This application is expected to strengthen the integrity and completeness of medical record data, as well as improve efficiency and accuracy in healthcare services.